2023
DOI: 10.1002/cncr.34812
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in prostate cancer screening, diagnoses, management, and outcomes between Indigenous and non‐Indigenous men in a universal health care system

Abstract: BackgroundIndigenous Peoples have higher morbidity rates and lower life expectancies than non‐Indigenous Canadians. Identification of disparities between Indigenous and non‐Indigenous men regarding prostate cancer (PCa) screening, diagnoses, management, and outcomes was sought.MethodsAn observational cohort of men diagnosed with PCa between June 2014 and October 2022 was studied. Men were prospectively enrolled in the province‐wide Alberta Prostate Cancer Research Initiative. The primary outcomes were tumor ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The authors showed that Indigenous men were less likely to have PSA testing performed in contrast to non-Indigenous community at all potential timeframes for PSA screening (Kiciak et al, 2023). Moreover, they enlightened that within Indigenous men community, the PSA was ≥10 ng/mL at diagnosis, suggesting the limited access of this community to PSA screening campaign (Kiciak et al, 2023). Finally, Creta et al examined the incorporation of mHealth into the clinical management of patients experienced benign condition such as lower urinary tract symptoms (LUTS) (Creta et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors showed that Indigenous men were less likely to have PSA testing performed in contrast to non-Indigenous community at all potential timeframes for PSA screening (Kiciak et al, 2023). Moreover, they enlightened that within Indigenous men community, the PSA was ≥10 ng/mL at diagnosis, suggesting the limited access of this community to PSA screening campaign (Kiciak et al, 2023). Finally, Creta et al examined the incorporation of mHealth into the clinical management of patients experienced benign condition such as lower urinary tract symptoms (LUTS) (Creta et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Arawaka et al conducted a randomized clinical trial assessing the effectiveness of mHealth professional consultation services in preventing postpartum depressive symptoms among 734 pregnant women living in Yokohama (Arakawa et al, 2023). Furthermore, Kiciak et al studied the PSA screening rates between Indigenous and non-Indigenous men collected within the Alberta Prostate Cancer Research Initiative (Kiciak et al, 2023). The authors showed that Indigenous men were less likely to have PSA testing performed in contrast to non-Indigenous community at all potential timeframes for PSA screening (Kiciak et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also support calls for more research on ways to address specific inequities not addressed by this guidance, such as prostate cancer in Indigenous and Black males. 244 , 245 …”
Section: Gaps In Knowledgementioning
confidence: 99%
“…Nous nous prononçons également en faveur de recherches plus approfondies sur la façon de lutter contre d’autres iniquités que le présent document n’aborde pas, par exemple, celle qui touche le cancer de la prostate chez les hommes autochtones et de race noire 246 , 247 .…”
Section: Connaissances à Parfaireunclassified